ANALISIS WACANA MEDIA TENTANG KEKERASAN TERHADAP PEREMPUAN DALAM BERITA TELEVISI - Darmayulis, Darmayulis (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2022)
Violence against women is a serious issue that is often reported by the television media, which has an important role in shaping public opinion. This study aims to analyze the representation of violence against women in television news and its impact on public perception. Through the approach of literature study and critical discourse analysis, this study examines the use of language, narrative, and visuals in news from various television stations in Indonesia. The results of the study show that news tends to use sensational language and explicit visuals, which can reinforce negative stereotypes and people's desensitization towards violence. Additionally, narratives that focus on victims' suffering often ignore the underlying social and structural context of violence. These findings indicate the need for more ethical and educational reporting practices to increase public awareness and understanding of violence against women, as well as encourage collective action to address this problem. The study also provides recommendations for the media, government, and NGOs to work together to create a safer and more supportive social environment for women.